Evaluation of prognostic indices in elderly hospitalized patients. Issue 6 (15th June 2016) - Monacelli, Fiammetta; Tafuro, Manuela; Molfetta, Luigi; Sartini, Marina; Nencioni, Alessio; Cea, Michele; Borghi, Roberta; Montecucco, Fabrizio; Odetti, Patrizio
Abstract : Aim: Prognosis informs the physician's decision‐making process, especially for frail older adults. So far, any non‐disease‐specific index has proven full evidence for routine use in clinical practice. Here, we aimed at assessing, prospectively, the calibration and discriminating accuracy of validated prognostic indices in a cohort of elderly hospitalized patients. Methods: This was a prospective observational study that enrolled elderly patients ( n = 100). The patients' assessment included clinical variables, as well as the following five prognostic indices of mortality: (i) Levine index (2007); (ii) Walter index (2001); (iii) CARING (C, primary diagnosis of cancer; A, ≥ 2 admissions to the hospital for a chronic illness within the last year; R, resident in a nursing home; I, intensive care unit admission with multiorgan failure, NG, noncancer hospice guidelines [meeting ≥ 2 of the National Hospice and Palliative Care Organization's guidelines]) criteria of Fischer (2006–2011); (iv) Silver Code of Di Bari (2010); and (v) Burden of Illness Score for Elderly Persons of Inouye (2003). Results: Patients' clinical characteristics: 70% women (age 86.20 ± 0.69 years), 30% men (age 85.40 ± 1.07 years), Comorbidity Illness rating scale (CIRS) 4.3 ± 0.61 and Barthel Index 28 ± 0.54. Walter and Burden of Illness Score for Elderly Persons scores showed similar prediction rates when compared with the expected validated values (ancova : F = 14.00, P < 0.008). Burden of Illness Score for Elderly Persons was the most calibrated and accurate index (receiver operating characteristic curve 0.72; P < 0.02). Conclusions: None of the assessed prognostic indices, in a "real world" scenario, afforded the optimal predictive accuracy (receiver operating characteristic curve 0.90); all these indices are still far from a robust answer to the prognosis in older age, reflecting a poor ability to encompass the spectrum of frailty. Effort should be made to tailor the prognostication in geriatrics, moving from a disease‐centered model to a precision model, tailored to the frail phenotype.Geriatr Gerontol Int 2017; 17: 1015–1021.